Impact of Magnetized water on phasiological and productive performance for quail - Rahawi, Ghadeer AbdAlMonem Mohammed (Journal of agricultural, environmental and veterinary sciences, 2022)
This current study was conducted to investigate the effects of magnetic water productive and some physiological parameters of quail. One hundred eighty birds divided into 3 groups, 3 replicates, 20 birds/ replicates. The study continued for (42 days). The 1st group (control) was reared on standard ration and tap water ,2nd and 3rd group reared on standard ration and drink magnetic treated water with strength (700 and 1400 gausses). Result statistical analysis of data showed a significant increase in body weight, weight again, feed conversion ratio, red blood cell, hemoglobin, packed cell volume, blood glucose level, total protein, improvement birds health indicate with H/L ration in 2nd and 3rd groups (treated with magnetic water) as compared with control, as well as a significant decrease in feed consumption, corpuscular hemoglobin, triglycerides, cholesterol level, albumin, ALT and AST enzyme. In conclude, the replacement of tap water with magnetic water enhance most of physiological and productive parameters of quail.
Keywords: magnetic water; quail; physiological parameter; productive parameter